The Influence of Motivation and Leadership on the Performance of Honorary Teachers through Work Discipline as a Mediation Variable at Tangerang Regency State High School - Yahya Rahayu; Nia Kusuma Wardhani (Dinasti International Journal of Management Science, 2023)
This research is based on the low performance of teachers in terms of the ability and professionalism of teachers in teaching and learning activities. The purpose of the study looked at the Influence of Motivation and Leadership on the Performance of Honorary Teachers through Work Discipline as a Mediation Variable in Tangerang Regency State High School. Quantitative research methods with data analysis methods are carried out with a Structural Equation Model or SEM approach based on Partial Least Square (PLS) is a structural equation model or SEM based on components or variants of Structural Equation Modeling (SEM). The sample studied was the entirety of the existing population, namely 80 honorary teachers of SMA Negeri 14, 20, and 21 in Tangerang Regency. Based on the analysis of this study obtained the results that 1) Motivation affects work discipline; 2) Leadership affects Work Discipline; 3) Work discipline affects the Performance of Honorary Teachers; 4) Motivation affects Teacher Performance 5) Leadership affects the performance of honorary teachers; 6) Motivation indirectly affects the performance of honorary teachers through Work Discipline; 7) Leadership indirectly affects the performance of honorary teachers through Work Discipline. In conclusion, teacher performance is influenced by motivation, work discipline and leadership.